A hybrid method for modelling damage in composites and its effect on natural frequency. (March 2019) - Suliman, B.; Featherston, C.A.; Kennedy, D.
Highlights: Hybrid method for modelling non-prismatic damage in composite plates. Efficient exact strip model for undamaged regions. Finite element model for regions containing damage. Hybrid method is around 4 times faster than pure finite element analysis. Parametric study of effects of damage on the lowest natural frequency. Abstract: Delamination is a frequent cause of failure in laminated structures, reducing their overall stiffness and hence their critical buckling loads. Delaminations tend to grow rapidly in postbuckling, causing further reductions in structural strength and leading ultimately to sudden structural failure. Many studies have investigated the effects of delaminations on buckling and vibration of composite structures. Finite element analysis is often used to model complex geometries, loading and boundary conditions, but incurs a high computational cost. The exact strip method provides an efficient alternative approach using an exact dynamic stiffness matrix based on a continuous distribution of stiffness and mass over the structure, so avoiding the implicit discretization to nodal points in finite element analysis. However due to its prismatic requirements, this method can model damaged plates directly only if the damaged region extends along the whole length of the plate. This paper introduces a novel combination of exact strip and finite element analysis to model more complex cases of damaged plates. Comparisons with pure finite element analysis and a previous smearing method demonstrate the capability and efficiency of this hybrid method for a range of isotropic and composite plates. The effect of damage on the lowest natural frequency is studied.